Hubungan iklim dan kondisi lingkungan fisik rumah terhadap insidensi demam berdarah dengue di beberapa zona musim di Daerah Istimewa Yogyakarta (Studi kasus di Kecamatan Kasihan, Kabupaten Bantul, Yogyakarta) - Farid Ayumi; Susi Iravati; Sitti Rahmah Umniyati (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Climate factors and conditions of physical environment house for the dengue fever incidence in several zone season in: a case study from Bantul, YogyakartaPurposeThis research aimed to determine the relationship between climate (rainfall, air humidity, and temperature) and physical conditions of house environment with incidence of dengue fever in some seasonal zones in Yogyakarta.MethodsThe design of this study was an ecological study by time to observe the trend of dengue incidence in Yogyakarta within the period of 2010-2014.ResultsResults showed not all ZOMs were related to the incidence of dengue fever in Yogyakarta. Environmental conditions of the physical house that have a correlation with the dengue fever were breeding place outside, while the use of gauze ventilation and the existence of mosquito larvae in-house, were not correlated to an occurrence of dengue fever.ConclusionRainfall, air humidity, and temperature have a correlation with the incident of dengue fever in some ZOM area. The condition of the physical environment of the house in the form of breeding places outside of the house is associated with the occurrence of dengue fever.